2019
DOI: 10.1093/wber/lhz048
|View full text |Cite
|
Sign up to set email alerts
|

The Profits of Wisdom: The Impact of a Business Support Program in Tanzania

Abstract: Business training programs in low-income settings have shown only limited impacts on firm revenues and profits, particularly for female entrepreneurs. A randomized design was used to compare the impacts of two types of business training programs targeting women with established small businesses in urban Tanzania. The basic version relied on in-class sessions to strengthen the participants’ managerial and technical skills. In the enhanced version, training was supplemented by visits from business coaches to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Larger effects for higher potential individuals is consistent with the calls for better targeting emerging from recent work. Having estimated no program effects for business training or workfare programs, some authors examined impact heterogeneity and concluded that a more careful targeting of businesses could improve the impacts these programs (e.g., Bardasi et al, 2021;Bertrand et al, 2021, and citations therein). The efficacy of SEED for youth with lower levels of education/ability remains untested and is an avenue we are planning on exploring.…”
Section: Discussionmentioning
confidence: 99%
“…Larger effects for higher potential individuals is consistent with the calls for better targeting emerging from recent work. Having estimated no program effects for business training or workfare programs, some authors examined impact heterogeneity and concluded that a more careful targeting of businesses could improve the impacts these programs (e.g., Bardasi et al, 2021;Bertrand et al, 2021, and citations therein). The efficacy of SEED for youth with lower levels of education/ability remains untested and is an avenue we are planning on exploring.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant resources devoted to training entrepreneurs in Africa, the impact of such programs has been modest, leading scholars, policy makers, and non-government organizations searching for insights into how to enhance training to be more impactful. Recent studies suggest a better match between the type of training and entrepreneur experience (Anderson et al, 2021;Bardasi et al, 2021;Berge & Pires, 2020) and gender (Bandiera et al, 2020;McKenzie & Puerto, 2021) may enhance the effectiveness of training programs. Other studies argue for better integration between training and ongoing mentoring (Bardasi et al, 2021), financial assistance (Berge et al, 2015), and psychological training (Bischoff et al, 2020;Campos et al, 2017) This research also contributes to the mindset learning literature (Dweck, 2006(Dweck, , 2015 in the African context, by examining growth mindset in the context of practicing entrepreneurs in Africa and not just students.…”
Section: Increased Understanding Of Necessity Entrepreneurship In The...mentioning
confidence: 99%
“…Recent studies suggest a better match between the type of training and entrepreneur experience (Anderson et al, 2021;Bardasi et al, 2021;Berge & Pires, 2020) and gender (Bandiera et al, 2020;McKenzie & Puerto, 2021) may enhance the effectiveness of training programs. Other studies argue for better integration between training and ongoing mentoring (Bardasi et al, 2021), financial assistance (Berge et al, 2015), and psychological training (Bischoff et al, 2020;Campos et al, 2017) This research also contributes to the mindset learning literature (Dweck, 2006(Dweck, , 2015 in the African context, by examining growth mindset in the context of practicing entrepreneurs in Africa and not just students. While scholars have examined growth mindset in both a poverty context (e.g., Burnette et al, 2018;Yeager et al, 2019) and an entrepreneurship context (e.g., Burnette et al, 2019), to the best of our knowledge none of these studies have examined both of these contexts together, nor have they been studied outside of the context of formal education settings.…”
Section: Increased Understanding Of Necessity Entrepreneurship In The...mentioning
confidence: 99%
See 2 more Smart Citations